Developing and Evaluating a Quality Improvement Intervention to Facilitate Patient Navigation in the Accountable Health Communities Model - Holcomb, Jennifer L.; Walton, Gretchen H.; Sokale, Itunu O.; Ferguson, Gayla M.; Schick, Vanessa R.; Highfield, Linda (Frontiers in Medicine, 2021)
Introduction: The Accountable Health Communities (AHC) model was designed to address the health-related social needs of Centers for Medicare & Medicaid Services beneficiaries. Bridge organizations across the AHC model have identified lack of technical assistance and peer planning as potential barriers to model success, particularly around patient navigation. The technical assistance and peer planning literature lacks an organizing, conceptual framework, but implementation science frameworks could serve as useful guides. The Strengthening Peer AHC Navigation (SPAN) research protocol seeks to fill this gap and will apply three implementation science frameworks, Consolidated Framework for Implementation Research, Intervention Mapping, and the Expert Recommendations for Implementing Change compilation, to develop a multi-level quality improvement intervention and evaluate the impact of peer planning on model outcomes. The aims of the SPAN study are to implement and evaluate a novel multi-level quality improvement intervention to improve AHC implementation and navigation milestones through structured peer planning and to provide successful technical assistance for the AHC model. Methods and Analysis: The quality improvement intervention is outlined in four Tasks: 1) Assessment - To conduct an assessment of each bridge organization’s current implementation, needs, and readiness in AHC model navigation activities; 2) Planning - To engage in a peer planning approach to build capacity for AHC model navigation activities; 3) Implementation with technical assistance - Co-creation of a quality improvement protocol for AHC model navigation activities; and 4) Evaluation - Measure the impact of the peer planning and technical assistance approach. Alongside the development and implementation of the quality improvement intervention, this protocol describes a mixed method, convergent parallel study design which will be used to evaluate whether the quality improvement intervention will lead to better outcomes. Tasks will be replicated with five bridge organizations participating in the AHC model. Discussion: This research protocol provides a framework that can be used to conduct structured peer planning with technical assistance for social needs programs. This study will provide data on both implementation and outcomes which eventually may impact healthcare cost and utilization.